Animal Reproduction in Veterinary Medicine - Aral, Faruk; Payan-Carreira, Rita; Quaresma, Miguel (Veterinary Medicine and Science, 2021)
Despite efforts to control udder health in cattle, are the causes of mastitis are on the rise. Although at first glance the birth process seems normal in domestic pigs, what could be the problem? What are the clinical aspects of the oestrus cycle and pregnancy endocrinology in mares? What is Lidia cattle breeding and clinic? Does calf gender affect milk yield? Do insecticides reduce fertility? Could boar pheromones be an option to stimulate sow reproduction? Animal Reproduction in Veterinary Medicine is a book with the answers to such questions. It includes 'Induction and Synchronization of Estrus', which describes the protocol principles and tools. The practical approach this book takes will help students, farmers, veterinarians and academics to build an understanding of the concepts and procedures required to answer real questions by comprehending the basic function of real clinic data. Humans often endure results from the misunderstanding that to be doing well, they should make each thing themselves.